Preface to the Iberoamerican Human-Computer Interaction Conference 2024 Special Issue - Maria Amelia Eliseo; Valéria Farinazzo Martins (CLEI Electronic Journal)
Preface to the Iberoamerican Human-Computer Interaction Conference 2024 Special Issue